The Critical Date for the Assessment of the Investor’s Nationality - Stanivuković, Maja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Abstract Several recent arbitral awards on jurisdiction in investment disputes have centred around the issue of the critical date for assessment of the individual investor’s nationality. While anonymously holding that an investor must be a foreign national at the time of the breach of the treaty and at the time of commencement of the arbitration, the tribunals were split on the relevance of the investor’s nationality on the date of investment. Although it seems that the ordinary meaning of most BITs requires diversity of nationality at the time the investor makes his investments, the apparently clear wording seems to be open to different interpretations. The author examines the reasons and circumstances that have led the tribunals to reach different conclusions with regard to the date of investment as the potentially critical date for assessing individual investor’s nationality under investment treaties.